Risk Stratification and Validation of Eleven Autophagy-Related lncRNAs for Esophageal Squamous Cell Carcinoma - Zhao, Xu; Wang, Yulun; Meng, Fanbiao; Liu, Zhuang; Xu, Bo (Frontiers in Genetics, 2022)
Purpose: Esophageal squama cell carcinoma (ESCC), the most prevalent subtype of esophageal cancer, ranks the sixth cancer-related mortality, making it one of the deadliest cancers worldwide. Identification of potential risk factors of ESCC might help implement precision therapies. Autophagy-related lncRNAs are a group of non-coding RNAs that perform critical functions in the tumor immune microenvironment and therapeutic response; therefore, we aim to establish a risk model composed of autophagy-related lncRNAs that can serve as a potential biomarker for ESCC risk stratification. Results: We utilized the lncRNA expression profile from 179 patients in the GSE53625 dataset as the training set and found 11 lncRNAs (AC004690.2, AC092159.3, AC093627.4, AL078604.2, BDNF-AS, HAND2-AS1, LINC00410, LINC00588, PSMD6-AS2, ZEB1-AS1, and LINC02586) that were co-expressed with autophagy genes and they were also independent prognostic factors by multivariate Cox regression analysis. The risk model was constructed with these lncRNAs, and the area under the receiver operating characteristic curve (AUC) of the risk model was 0.728. To confirm that the model is reliable in other datasets, analysis using 174 patients from the TCGA database was performed as the testing set and the AUC value was 0.724. Conclusion: The lncRNA risk model we constructed provides a useful tool in risk stratification and predicting the prognosis of ESCC patients.